2011
DOI: 10.5152/tud.2011.066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ureteric jet flow with Doppler ultrasonography during manual compression

Abstract: Objective: This study aimed to distinguish between obstructive and non-obstructive dilation of the upper urinary tract using ureterovesical jet flow analysis with Doppler ultrasonography (US) and manual flank compression. Materials and methods:The study enrolled 54 patients (11 women, 43 men; mean age 27.5 years) with unilateral hydronephrosis. All but 2 pregnant patients underwent the Doppler US and the reference standard test [intravenous pyelogram (IVP)] after standardized hydration. The distended urinary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has been suggested that absence of jets should be confirmed in contralateral decubitus patient position. 7 MRI utilizes nonionizing radiation, and provides high sensitivity and specificity without the need for contrast. 20 MRI is confirmed as a safe imaging method, with no known teratogenic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that absence of jets should be confirmed in contralateral decubitus patient position. 7 MRI utilizes nonionizing radiation, and provides high sensitivity and specificity without the need for contrast. 20 MRI is confirmed as a safe imaging method, with no known teratogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that absence of jets should be confirmed in contralateral decubitus patient position. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation